Ezra, Nehemiah, and Esther: restoring the church - Benn, Wallace (Crossway, 2021)
"These neglected books of the Bible teach us about God's steadfast love toward his people and his deliverance of them. They are about how God keeps his promises and restores his Old Testament people after the sad and difficult years of the Exile"--